GENDER RELATIONS IN THE SUDANESE FAMILY VS. ISLAMIC FOUNDATIONS: A SOCIOLOGICAL ANALYSIS STUDY (Lex localis - Journal of Local Self-Government, 2024)
This study examines the intersection of Islamic principles and Sudanese cultural practices in shaping gender relations within the family. Using a comparative analytical approach, it explores how key Islamic texts, including the Quran and Hadith, define gender roles and responsibilities, and compares these foundations with the lived realities of Sudanese families. Data was collected through content analysis of Islamic religious texts, social reports, and scholarly literature on gender relations in Sudan and Islam. The research focuses on the contemporary context while tracing historical shifts in Sudanese family dynamics amidst the nation’s cultural and social diversity.Findings reveal that Islam emphasizes equality in rights and responsibilities between men and women, promoting role complementarity within the family. However, gender relations in Sudanese families are shaped by a complex interplay of cultural, social, and economic factors. While Islamic principles align with many Sudanese cultural norms, local traditions often exert a stronger influence, particularly in rural areas where women may experience subordinate roles despite Islamic teachings advocating equality.This study contributes to a deeper understanding of how religion and culture interact to shape family dynamics, highlighting the nuanced and evolving nature of gender relations in Sudan. The findings underscore the need for a balanced approach that respects cultural diversity while aligning with the egalitarian principles of Islam.